Pengembangan Media Komik Legenda Gunung Pinang untuk Meningkatkan Kemampuan Literasi Budaya Peserta Didik Fase B - Jumyati Jumyati; Yuyu Yuhana; R. Ahmad Zaky El Islami (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to analyze and describe the feasibility and student responses to the Legenda Gunung Pinang comic media in an effort to improve the cultural literacy of phase B students at SDN Pasir Gadung. The study used the Research and Development method with the ADDIE model. Quantitative data came from the results of validation by cultural experts, media experts, and elementary education experts, as well as student response questionnaires. Qualitative data were obtained from notes, suggestions, and comments from validators and students. The research instruments included interview guidelines, observations, and questionnaires. The results of the study showed: 1) The media validated by cultural experts was very feasible with a percentage score of 97%; 2) The media validated by media experts was very feasible with a percentage score of 94.73%; 3) The media validated by elementary education experts was very feasible with a percentage score of 87.5%; 4) The response of students to the Legenda Gunung Pinang comic media was very good with a percentage score of 94%. Therefore, the Legenda Gunung Pinang comic media is very feasible to be used in the learning process to improve the cultural literacy of phase B students.